AN EFFICIENT METHOD OF ANALYSIS OF CO-PLANAR DIPOLE ARRAY ANTENNAS - Imoro, A. I. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Generalized impedance formulas for non-uniform array configurations based on the improved Circuit Theory (ICT) are presented for the first time in an English text. To further enhance the ICT as an accurate and fast method for evaluations, a new and more com pact closed-form formula is derived to replace a function requiring time intensive numerical integration during the implementation of the of the ICT algorithm in co-planar dipole array antenna evaluations. The resulting ICT computational scheme reduces the required CPU time by a factor of two and has the same order of accuracy as the conventional MoM. The new ICT implementation would be of considerable use as a Computer Aided Design (CAD) tool of co-planar dipole array antennas. [Vol. 11, No. 3 (1996), pp 44-54]